United States : Selected Issues. (IMF Staff Country Reports; Country Report, 2012)
This Selected Issues paper for the United States discusses the microeconomics of the country-household wealth and savings. Households' consumption-saving decisions have an important bearing on the U.S. economic outlook. This paper demonstrates how households with consistently lower income, which have shown growth in the years prior to the crisis, experienced larger declines in their saving rates and a larger rise in their indebtedness before the crisis, contributing significantly to the dynamics of the mean saving rate.